2020
DOI: 10.1016/j.mehy.2020.109757
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and anosmia in Tehran, Iran

Abstract: Patients with acute olfactory disorders typically present to the otolaryngologist with both acute hyposmia and less often with anosmia. With the onset of COVID-19 we have noticed an increase in the number of patients who have presented with new onset of complete smell loss to the senior author's practice in Tehran, Iran. This anosmia and the frequency with which patients present is highly unusual. Coronaviruses have been known to cause common cold symptoms. COVID-19 infections have been described as causing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 11 publications
(12 reference statements)
5
78
0
9
Order By: Relevance
“…The damage SARS-CoV-2 in icts on taste and smell must be different from that of other viruses, but the pathophysiological mechanisms are largely unknown. Gilani et al [7] hypothesized that the mechanism of injury is similar to that of other coronaviruses infections that cause central and peripheral neurologic de cits, but we agree with Vaira et al [8] when they suggest that, given the high rate of rapid recovery, it is reasonable to hypothesize that the OD is not related to de nitive damage from the virus to the neuronal cells, and a damage to other cell types appears more likely. In case of SARS-CoV-2-induced anosmia, magnetic resonance imaging of the olfactory bulb did not show abnormal ndings regarding its volume or signal intensity [9].…”
Section: Discussionsupporting
confidence: 77%
“…The damage SARS-CoV-2 in icts on taste and smell must be different from that of other viruses, but the pathophysiological mechanisms are largely unknown. Gilani et al [7] hypothesized that the mechanism of injury is similar to that of other coronaviruses infections that cause central and peripheral neurologic de cits, but we agree with Vaira et al [8] when they suggest that, given the high rate of rapid recovery, it is reasonable to hypothesize that the OD is not related to de nitive damage from the virus to the neuronal cells, and a damage to other cell types appears more likely. In case of SARS-CoV-2-induced anosmia, magnetic resonance imaging of the olfactory bulb did not show abnormal ndings regarding its volume or signal intensity [9].…”
Section: Discussionsupporting
confidence: 77%
“…The included studies consist of a variety of study designs -cross-sectional (n = 22) (12,(16)(17)(18)(19)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41); case-control (n = 3) (42-44); casereport and case series (n = 3) studies (45)(46)(47). Two categories of the MMAT were employed based on the study design to examine the methodological quality of these studies; quantitative non-randomized category for cross-sectional and case-control studies and quantitative descriptive category for case-report and case series ones.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The most common method was the self-report. Self-report could be done through different ways: an online questionnaire (12,19,27,30,34,37), non-online questionnaire (18,32,35,39,43,44), online checklist (17), the COVID RADAR Symptom Tracker app (16), visual analogue scale (VAS) (25), archived medical records (40,41), or verbally (45,46). Four studies (28,29,31,33) did not report how to measure, just extracted from medical records.…”
Section: Olfactory and Gustatory Dysfunction Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, there have been an increment in the scienti c studies from various parts of the world about the signi cant increase in the cases number presenting with loss of smell alone. Gilani et al from Iran reported 8 patients with anosmia, 5 of them were con rmed cases of COVID-19, and the remaining 3 cases were not tested owing to the shortage of testing kits in the pandemic period [7]. An European multicenter study concluded that olfactory (85.6%) and gustatory (88%) abnormalities are prevalent symptoms in European con rmed COVID-19 cases, who may not have other nasal complaints [8].…”
Section: Introductionmentioning
confidence: 99%